From Classroom to Screen: Resilience and Experiences Encountered by Nursing Educators in Transitioning to Online Learning amid the Pandemic - Arrojo, Alyssa Marie; De Paz, Oscar; Pulgarinas, Romeo Jr. (JPAIR Institutional Research, 2025)
The COVID-19 pandemic has had a profound impact on education worldwide, particularly in regions that rely heavily on traditional face-to-face teaching. The abrupt transition from face-to-face teaching to online teaching presented both challenges and opportunities for nursing educators. This qualitative descriptive study examined the experiences of nine nursing educators from selected nursing schools in the Visayas region, with a focus on the challenges they encountered during this transition. Data were collected through in-depth interviews and analyzed using Graneheim and Lundman (2004). Ensuring rigor through verification, validation, and validity checks. Analysis of 21 significant statements revealed three overarching themes: Experiences, Feelings, and Effects. Participants reported external challenges such as limited access to computers, mobile devices, and reliable internet connectivity, alongside predominantly negative emotions including stress, anxiety, and self-doubt. Despite these obstacles, educators demonstrated adaptability, resilience, and professional growth, which was facilitated by both institutional support and personal perseverance. The study highlights the complex interplay of challenges and coping strategies during educational transitions, underscoring the importance of structured support and capacity-building initiatives for educators.
Keywords: Nursing educators; face-to-face; online learning; qualitative descriptive research; educational transition; pandemic; Philippines